Convenient fictions and inconvenient truths: Dilemmas of diversity at three leading accountancy firms. (March 2016) - Ashley, Louise; Empson, Laura
Abstract: We draw on comparative research conducted at three leading UK accountancy firms to ask, is the business case for diversity fatally flawed in relation to gender and flexible work? The business case has proved controversial in the academic literature, where it is said to have displaced the moral case and justified the enactment of ritual around diversity rather than generate substantive change. Studies suggest that within the accountancy sector both cases are subsumed beneath a strong 'client service ethic, ' deployed to justify long hours and support the status quo. We show that the business case for diversity has made a limited contribution to transformational change because it is based on the retention of talent, when perceived competitive advantage and career progression rest on temporal commitment to work. For accountancy firms, this finding may represent an inconvenient truth. However, the business case can also encourage engagement with underlying narratives surrounding gender and equality, and thus represent a convenient fiction, contributing towards incremental change.